Some Properties of Cement Mortar Modified by Styrene Butadiene Rubber (Journal of Engineering, 2023)
This research studies the effect of adding five different percentages of polymer (2, 4, 6, 8, and 10% of cement weight) on cement mortar's fresh and hardened properties, which was cured at laboratory temperature for 7, 14, and 28 days. Workability increases with increasing polymer. The workability value was lowest (25.6 and 29.4) % in mixtures containing 2% and 4% of (SBR). Increasing polymer ratios significantly decreased mechanical properties (compressive and flexural strength). Therefore, the best results were at 2% SBR and 4% SBR at 28 days of age. An inverse relationship was recorded between the increase in SBR ratios and polymer-modified cement mortar's compressive and flexural strength values. In general, the highest improvement in the water absorption and dry density resulted in better results with a decrease in the proportion of the polymer for all specimens of cement mortar containing 4% SBR polymer relative to the reference mixture.